Impacto de las tic’s en los cambios socio-culturales de los estudiantes de octavo año de educación general básica paralelo “a” de la Unidad Educativa Once de Noviembre de la parroquia Ignacio Flores, cantón Latacunga, provincia de Cotopaxi durante el periodo 2014-2015 - Chicaiza Orozco, Irene Magali (2015)
The general aim of this investigation was to determine the influence of the Communication and Information Technologies in the Intercultural Changes of students of General Basic Education in the “Once de Noviembre” Education Center, Ignacio Flores Parish, Latacunga Canton, Cotopaxi Province during the academic period 2014-2015. The problem was investigated how:’¿Than strategies must be implemented to the proper management of the Communication and Information Technologies? .The methodology used was of type bibliographic and the of fiel and ode level descriptive; to detail the nature of the problem of study. The conclusions reached were: sometimes teachers use technology resources and students consider that the human being is the main axis in the technological and social changes. The contribution of this work is the development of training workshop on the proper use of technological tools, providing an educational tool for teachers within the teaching and learning process.